Almacenamiento de carbono en un bosque de Pinus pseudostrobus en Nuevo San Juan, Michoacán - Ordóñez, José Antonio; de Jong, Bernardus H.J.; Masera, Omar (Instituto de Ecología, A.C., 2016)
In this work, the CO2Fix dynamic model for Windows Ver. 1.2 was utilized to obtain the potential carbon sequestering in the community Nuevo San Juan. Total carbon estimated in the long run (250 years) was 217 tC/ha; the biomass (aerial and subterranean) with 74 tC/ha, products with 49 tC/ha and soil with 94 tC/ha. It was estimated that in the same time span, there is a potential for carbon sequestering in the community forest of 1.9 MtC in tis 8,870 ha. At the same time, sensitivity analyses were carried out with three parameters to identify the potential difference in carbon sequestering (life time of the wood products, humification and decaying rates ±30 % of the original value). Finally, the importance of using the CO2Fix model as a tool for forest management is highlighted especially for forest plantations. The simulation was based, as feasible, in data available locally: (a) area surface in study; (b) forest management: thinning cycles, regeneration and liberation cuttings ; actual standing volume and volume extracted; (c) tree growth: current annual increment, diameter, height, age and annual average increment and, (d) manufactured products as: paper, packaging, construction lumber, wood for furniture, fire wood and dead wood.